Pengaruh internet sebagai sumber belajar dan kemandirian belajar terhadap pemahaman materi pelajaran ekonomi kelas X dan XI SMA Jawaahirul Hikmah Besuki tahun ajaran 2020/2021 - Pradani, Ferdina Putri; Sulastri Rini Rindrayani (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2022)
The Effect of the Internet as a Source of Learning and Independent Learning on Understanding Economics Class X and XI SMA Jawaahirul Hikmah Besuki Academic Year 2020/2021. The purpose of this study was to determine the effect of the internet as a source of learning and independent learning on the understanding of subject matter for students in class X and XI at SMA Jawaahirul Hikmah Besuki. The type of research used is quantitative with a survey approach. The results of this study are: (a). There is a partial influence between the independent variables of the internet as a learning resource (X1) on the understanding of economics subject matter (Y), namely tcount 3.858 > ttable 1.682 which means significant, (b). There is a partial effect between the independent variable learning independence (X2) on the understanding of economics subject matter (Y), namely tcount 3.359 > ttable 1.682 which means significant, and (c). There is a simultaneous influence of the independent variable of the internet as a learning resource (X1) and the independent variable of learning independence (X2) on the dependent variable of understanding economics subject matter (Y), namely fcount 19,419 > ftable 3,220 which means significant. Then the contribution given is 48.6% and the remaining 51.4% is influenced by other variables. The conclusion is that there is a partial influence on the internet as a learning resource (X1) on the understanding of economics subject matter (Y) and independent learning (X2) on the understanding of economics subject matter (Y) for students of class X and XI SMA Jawaahirul Hikmah Besuki Academic Year 2020 /2021 with a contribution of 48.6%.